2009
DOI: 10.2136/vzj2008.0040
|View full text |Cite
|
Sign up to set email alerts
|

Flow Dimension and Anomalous Diffusion of Aquifer Tests in Fracture Networks

Abstract: Characterization and modeling of aquifers is particularly challenging in fractured media, where flow is concentrated into channels that are poorly suited to traditional approaches to analysis. The generalized radial flow model is an alternative method for hydraulic test interpretation that infers an additional parameter, the flow dimension n, to describe the flow geometry. This study was a Monte Carlo analysis of numerical models of aquifer tests in two‐dimensional fractured media, with the objective of unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…11a). Additional analysis can be applied for further model evaluation like flow dimension analysis as indicated by, for example, Walker et al (2003), Maréchal et al (2008), and Cello et al (2009).…”
Section: Comparison With Measured Datamentioning
confidence: 99%
“…11a). Additional analysis can be applied for further model evaluation like flow dimension analysis as indicated by, for example, Walker et al (2003), Maréchal et al (2008), and Cello et al (2009).…”
Section: Comparison With Measured Datamentioning
confidence: 99%
“…DFNs mimic natural fractured media by representing each fracture individually. They have first been designed toward homogenizing fractured media [ Long et al , 1982], and further applied to understanding the flow structures of complex fracture networks [ Davy et al , 2006a; de Dreuzy et al , 2001b, 2001c, 2002, 2004a; Le Goc et al , 2010; Leung and Zimmerman , 2010], permeability and dispersivity upscaling [ Baghbanan and Jing , 2007; Charlaix et al , 1987; de Dreuzy et al , 2001a, 2010; Frampton and Cvetkovic , 2007, 2009; Mettier et al , 2006; Park et al , 2001; Snow , 1969] and, more generally, the definition of the right modeling approach [ Cello et al , 2009; Davy et al , 2006a; Ji et al , 2011; Jourde et al , 2007; Long and Witherspoon , 1985; Painter and Cvetkovic , 2005; Sahimi , 1993]. As a further interest, DFNs can extract key information on flow properties from the large geological and geophysical data available on fracture media [ Bonnet et al , 2001; Davy et al , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated that fractal fracture networks give rise to fractional flow (Acuna and Yortsos 1995, Doughty and Karasaki 2002, de Dreuzy and Davy 2007, Cello et al 2009). In non-fractal fracture networks both Euclidean and fractional flow can occur.…”
Section: The Grf Modelmentioning
confidence: 99%